PROBLEMS OF TRAINING TEACHERS AND STUDENTS FOR PROJECT ACTIVITIES ON THE EXAMPLE OF THE ROSTOV REGION (EDUCATION IN THE 21ST CENTURY, 2023)
The article discusses the issues of the formation of additional education programs "mentoring in a group of project activities" intended for teachers working with educational projects. The need to implement project-based learning within the framework of a modern school comes from the requirements of federal state educational standards and the request of the economy for the training of graduates with certain developed competencies, in particular, capable of making independent decisions, planning their own time, working in a team and acting in conditions of uncertainty. However, the introduction of project-based learning into practice rests on a number of difficulties and limitations, which are considered in this paper.The article presents the results of a survey of teachers and students, which allowed us to establish what main difficulties they face in the process of creating educational projects. In addition, it is determined what kind of support teachers need to successfully conduct project activities, and how the interaction of project training participants with the external environment (public, private enterprises and institutions) is implemented. The survey is based on the analysis of the works of researchers devoted to the problem of implementing project-based learning in the educational process P. N. Drobot, K. Watson, P. Lindholm, E. D. Melchenko, S. V. Melchenko, A. A. Kolev, A.V. Marina, S.N. Trifonova, E.F. Malafeeva and I. A. Yurlovskaya. The results of the study will become the basis for the creation of a program of additional professional education "Mentoring in group project activities", the implementation of which is planned on the basis of the Southern Federal University.Resume1. As the study showed, the level of dissemination of work with educational projects among teachers of the Rostov region is quite high (94%), however, 42% of students were not involved in project training, which indicates insufficient dissemination of project activities in their environment during the implementation of the educational process.2. The level of communication of educational organizations with the external environment in the process of implementing project activities is high, since 77% of teachers implement external interaction when creating educational projects, but only 5% of teachers involve private companies in working with educational projects, which does not allow creating project products that are close to the requirements of real modern commercial projects.3. At the same time, teachers of the Rostov region do not have sufficient competencies to work with educational projects, since the main way of forming their project competence is self-education (89%), in addition, among them there is a high need for methodological (51.4%) and educational (30.4%) support in the implementation of project training, which indicates a lack of knowledge and skills to work with educational projects in the pedagogical environment.4. The demand by teachers for additional education programs devoted to the basics of project activity is also high, which is confirmed by the desire of 50% of respondents to develop project competence in the process of passing advanced training programs.5. The basis of the future program of additional professional education will be the topics identified by teachers and students as the most difficult to implement within the framework of project training, including: the project, its concept; relevance, practical significance and novelty of the project; goals and objectives of educational projects; design stages; features of working with project teams; project documentation: its types and rules of compilation; project protection and preparation for it; team reflection.6. The survey also opens up new horizons of research, since it leaves unresolved questions about the interaction of teachers and students with the external environment in the process of implementing educational projects. It is necessary to study the readiness of non-governmental organizations and private companies to participate in joint projects, possible options for such interaction and its limitations.
Keywords: Key words: additional professional education, continuing education, project activity, group project activity, project competence.